Human herpesvirus 6 viremia affects T-cell reconstitution after allogeneic hematopoietic stem cell transplantation - Coco de Koning; Rick Admiraal; Stefan Nierkens; Jaap Jan Boelens (Blood Advances, 2018)
Abstract: Human herpesvirus 6 (HHV6) viremia is a common cause of morbidity following allogeneic hematopoietic cell transplantation (HCT). We previously associated T-cell reconstitution with HHV6 viremia. Here, we investigated whether HHV6 viremia affects T-cell reconstitution after HCT in a time-dependent retrospective analysis. We included 273 pediatric patients (0.1-22.7 years; median follow-up, 58 months) receiving a first HCT between 2004 and 2014. HHV6 was screened weekly in plasma via polymerase chain reaction and occurred in 79 patients (29%) at a median time of 19 days after transplant. Main outcome of interest was immune reconstitution (IR) (CD3/CD4/CD8 T cells), measured biweekly until 12 weeks and monthly thereafter. Cox proportional-hazard models were used with IR and HHV6 as time-dependent variables in multivariate analysis with serotherapy in conditioning, graft source, graft-versus-host disease, age, and other viruses (Epstein-Barr virus, cytomegalovirus, and adenovirus) as covariates. Only patients with very high HHV6 viremia (>105 copies/mL) showed hampered CD4+ (hazard ratio [HR], 0.913; 95% confidence interval [CI], 0.892-0.934; P < .001) and CD8+ (HR, 0.912; 95% CI, 0.891-0.933; P < .001) reconstitution in comparison with patients without HHV6, from ∼6 months after HCT. Especially naïve CD4+ IR was affected (P = .028) but not effector memory CD4+ IR (P = .33). Interestingly, T-cell reconstitution was improved in patients treated with antivirals (HR, 1.572; 95% CI, 1.463-1.690; P < .001). These findings suggest that HHV6 viremia affects late but not early T-cell reconstitution.